Religious Terrorism - Reza Kavosh (Andalas Journal of International Studies (AJIS))
This article explores religious terrorism, a concept that has received a lot of attention from academics and the international community. It briefly looks at the definitions of terrorism and religious terrorism, in order to give clarity to the rest of the article. The article presents two sides of a debate. One side is that religious terrorism is in fact a unique and separate phenomenon. The other side is that “religious terrorism” is not fundamentally different from terrorism, and rather is a misrepresentative term made up by academics in the West in order to further their political agenda... The authors argue that even if some people to justify violent acts use religion, nevertheless the basic tenets of most religions are peace and tolerance. Religion has the potential to prevent, mediate, and resolve conflict, as well as heal and reconcile after violence has occurred. In order to counter terrorism, religious leaders need to work tirelessly around the world to uphold the peaceful aspects of religion.